2012
DOI: 10.1016/j.ijer.2012.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of increased self-regulated learning opportunities on student teachers’ metacognitive and motivational development

Abstract: This intervention study focused on the relationships between student teachers' self-regulated learning (SRL) opportunities, their use of metacognitive learning strategies and their motivation for learning. Results indicate that student teachers' use of metacognitive learning strategies increases significantly in learning environments with increased SRL opportunities. In opposite to these findings, no significant difference was shown between student teachers' motivation for learning before and after the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 41 publications
1
19
0
1
Order By: Relevance
“…t value of self regulated learning variable is 0.047 smaller than 0.05 so that independent variables of self regulated learning significantly influences HOTS dependent variable at alpha 5%. The results of this study are in accordance with the findings and opinions of Hendrian, et al (2017), Venty, Budiyono & Slamet (2016), Vrieling, Bastiaens, &Stijnen (2012), andFadlelmula, Cakiroglu, &Sungur (2015) explaining that self regulated learning can affect students cognitive (HOTS). One of the stages in self regulated learning is performance control.…”
Section: Resultssupporting
confidence: 92%
“…t value of self regulated learning variable is 0.047 smaller than 0.05 so that independent variables of self regulated learning significantly influences HOTS dependent variable at alpha 5%. The results of this study are in accordance with the findings and opinions of Hendrian, et al (2017), Venty, Budiyono & Slamet (2016), Vrieling, Bastiaens, &Stijnen (2012), andFadlelmula, Cakiroglu, &Sungur (2015) explaining that self regulated learning can affect students cognitive (HOTS). One of the stages in self regulated learning is performance control.…”
Section: Resultssupporting
confidence: 92%
“…Only then, increased SRL opportunities for TCs can result in more motivated TCs and increased use of metacognitive skills. Contrary to the importance of linking content with metacognition in courses, in the Netherlands many educational programs in primary teacher education display a gap concerning SRL opportunities between the major (first two years, mainly teacher-controlled) and minor (final two years, mainly student-controlled) phase of learning programs (Vrieling, Bastiaens, and Stijnen 2012b).…”
Section: Knowledge Buildingmentioning
confidence: 93%
“…It concerns an explication of teaching behaviors that are expected in SRL learning designs and represents a way of teaching that facilitates students' use of SRL skills. Through the connection of theoretical and empirical findings of five earlier performed studies in primary teacher education (Vrieling, Bastiaens, and Stijnen 2010, 2012a, 2012b, 2012c, 2013), a conceptual model is described first (Section 2) that comprises necessary ingredients for effective learning environments with balanced student-and teacher-control (i.e. 'SRL balance').…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Vrieling, Bastiaens, and Stijnen, (2012) indicated that level of metacognitive learning strategies increased with increased SRL opportunities in education programs. Several factors influence participants' motivation for learning that should be considered (1) creating an adequate knowledge by gradually increasing SRL opportunities; (2) giving attention to the conditions that can hinder or foster SRL (3) support student teachers' collaborative learning and (4) develop appropriate learning tasks.…”
Section: The Lms Qualitymentioning
confidence: 99%